ANALISIS PENDAPATAN USAHATANI PADI PADA PROGRAM PETANI MAKMUR DI KECAMATAN TEMPURAN KABUPATEN KARAWANG - Dwinesa Aprilia Prastami; Abubakar Abubakar; Lutfi Afifah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
Rice is one of food crop commodities with the highest production yields in Karawang Regency, which corresponds to the large number of agricultural workers. Because of the large number of farmers who own rice farms, PT Pupuk Kujang Cikampek has invested in efforts to help the farmers prosper. The purpose of this study is to compare the revenue costs and income obtained in rice farming between before and after participation in the “Program Makmur” in order to assess the feasibility of rice farming based on R/C Ratio and BEP. The research topic was chosen on purpose (intentionally). Purposive sampling was used to collect information from 30 farmers. The descriptive method was used in this research, which is quantitative in nature. The research was conducted from Desember 2022 to Januari 2023. The results showed that GKP production in Lemahkarya Village and Sumberjaya Villages howed a comparison before and after participating in the "Program Makmur" that the average revenue received by farmers was IDR 20,222,560.98/ha/planting season to IDR 21,155,081.30/ha/planting season, with an average income received of IDR 7,165,567.07/ha/planting season to IDR 8,112,794.72/ha/planting season. As a result, it is possible to conclude that rice farming is possible to be cultivated. Key words: farming, feasibility, income, paddy, profit